Physical education in schools, sport activity and total physical activity in adolescents - Nakamura, Priscila Missaki [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Papini, Camila Bosquiero [UNESP]; Lemos, Natalia De [UNESP]; Nazario, Murilo Eduardo Santos [UNESP]; Kokubun, Eduardo [UNESP] (Universidade Federal de Santa Catarina, 2013)
Less than half of adolescents reach the recommended 300 minutes per week of physical activity (PA). Physical education classes and sports participation provide opportunities for adolescents to accumulate more time for PA practice; however, little is known about the influence of these variables on the level of total physical activity of adolescents. The aim of this study was to investigate the association between the practice of physical education (PE) in schools and sports activities (SA) with the practice of total PA of adolescents. The study was cross-sectional and involved 467 adolescents of high school (15.8 ± 0.9 years-old) from the city of Rio Claro, in the State of São Paulo. Participants completed the Physical Activity Questionnaire to Older Children (PAQ-C) and questions related to the practice of PE and SA in schools. We performed a logistic regression with p<0.05 using SPSS. Girls had lower prevalence of PA than boys, 9.4% and 26.8%, respectively. Boys who did not participate of PE classes (OR=0.25, 95% CI=0.09-0.66) and SA in schools (OR=0.34, 95% CI=0.12-0.95) were less likely to be active in PA than boys who practiced these activities. The participation in PE classes or engagement in some SA were positively associated with the practice of total PA in boys.

Menos da metade dos adolescentes atingem a recomendação de 300 minutos por semana de Atividade Física (AF). As aulas de Educação Física e participação de esporte proporcionam oportunidades para os adolescentes acumularem mais tempo para a prática de AF, entretanto, pouco se sabe sobre a influência dessas variáveis no nível de AF total dos adolescentes. O objetivo do estudo foi verificar a associação entre a prática de Educação Física Escolar (EFE) e Atividades Desportivas (AD) com a prática de AF total em adolescentes. O estudo foi transversal e participaram 467 adolescentes do Ensino Médio (15,8 ± 0,9 anos) da cidade de Rio Claro-SP. Os participantes preencheram o Physical Activity Questionnaire to Older Children (PAQ-C) e questões relacionadas com a prática de EFE e AD. Foi realizada a Regressão Logística com p<0,05 através do SPSS. Meninas apresentaram menor prevalência de AF do que os meninos, 9,4% e 26,8% respectivamente. Meninos que não realizaram EFE (RO=0,25; 95% IC= 0,09-0,66) e AD na escola (RO=0,34; 95% IC=0,12-0,95) apresentaram menores chances de serem ativos na AF total do que os meninos que praticaram essas atividades. A participação das aulas de EFE ou a prática de alguma AD foram associadas positivamente com a prática de AF total nos meninos.
Educação física escolar, atividade desportiva e atividade física total em adolescentes
Keywords: Adolescentes; Atividade física; Educação física; Adolescents; Physical activity; Physical education